Optimisation of immobilised cellulase onto carbon nanotubes using response surface methodology - Rasha, Mohammed Abd; Nour, A. H. (Academic Journals, 2012)
Although, the cellulase enzyme can work with high catalysis under mild condition, however, it does not fulfill the industry requirement. In this study, cellulase obtained from the fermentation of sewage treatment plant (STP) sludge by Trichoderma reesei RUT C-30 was covalently immobilised on functionalised multi-wall carbon nanotubes (MWCNTs). Statistical optimisation using the PlackettBurman design (PBD) method was implemented to identify parameters with significant effects on the process of immobilisation. The results obtained from this PBD showed that three parameters have a significant effect on immobilisation: pH, temperature and N-ethyl-N-(3-dimethyl aminopropyl) carbodiimide hydrochloride (EDC) concentration. Based on our PBD results, these parameters were further optimised using a face-centred central composite design (FCCCD). The resulting optimum conditions for cellulase immobilisation, as determined by FCCCD, were pH 4.5, 30°C and 1 ml of 10mg/ml EDC. The amount of immobilised cellulase was approximately 98% using these optimum conditions. The resulting MWCNT-cellulase composite was further characterized by Fourier transform infrared spectroscopy (FTIR) technique.